1988
DOI: 10.1007/bf01287264
|View full text |Cite
|
Sign up to set email alerts
|

Beta-decay of148,150,152Pr into levels of148,150,152Nd

Abstract: The/?--decay of 14 s, 15 o, 1 s 2pr into levels of 148,1 s o, 1 s 2Nd has been studied by y-singles, y y-coincidence and for 148pr also by y y-angular correlation measurements. The praseodymium activities have been obtained by thermal neutron-induced fission of z35U followed by on-line mass separation with the helium-jet coupled mass separator HELIOS. Decay schemes for these heaviest praseodymium nuclides are proposed. From the angular correlation measurements spin values for the seven lowest levels of 148Nd a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[6][7][8]10,11] [9]. The excitation energy of the band head energy at or above the paring energy gap indicates that this assignment is possible [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8]10,11] [9]. The excitation energy of the band head energy at or above the paring energy gap indicates that this assignment is possible [9].…”
mentioning
confidence: 99%
“…Previously, the level structure of 152 Nd has been studied by using various experimental methods [6][7][8][9][10][11][12]. The ground-state band and a negative-parity band based on a 2 − state have been identified.…”
mentioning
confidence: 99%
“…This is reasonable because levels in 152 Pr populated in the beta-decay of the even-even 152 Ce nucleus cannot have spins larger than three when the ground sate spin of 152 Pr is either 3 or 4 [7][8][9][10]. The levels observed in the spontaneous fission of 252 Cf have usually high spins.…”
mentioning
confidence: 93%
“…Previously, fourteen low-lying excited levels in 152 Pr were identified in the beta-decay of 152 Ce [6] where an isomer at 114.8(2) keV was found with a half-life of 4.1(1) µs. The configurations of the ground state of 152 Pr were discussed in the reports of the beta-decay of 152 Pr to 152 Nd [7][8][9][10] with different assignments. However, no high-spin level has been observed in 152 Pr before the present work.…”
mentioning
confidence: 99%
“…From y-ray spectra of mass separated fission products produced by KUR-ISOL , the Pr-K X-rays and two y-rays are assigned to be generated by the B- [2] showed that this y-transition belongs to the B-decay of 152pr. The search for 152Ce has been carried out again in the present report.…”
mentioning
confidence: 99%